(untitled) (Journal of Engineering, 2022)
Turbidity is a visual property of water that expresses the amount of suspended substances in the water. Its presence in quantities more significant than the permissible limit makes the water undrinkable and reduces the effectiveness of disinfectants in treating pathogens. On this basis, turbidity is used as a basic indicator for measuring water quality. This study aims to evaluate the removal efficiency of AL- Muthanna WTP. Water turbidity was used as a basic parameter in the evaluation, using performance improvement evaluation and data from previous years (2016 to 2020). The average raw water turbidity was 26.7 NTU, with a minimum of 14 NTU, with a maximum of 48 NTU. Water turbidity value for 95% of settling daily reading data was (13.7) NTU which is larger than the goal value (10) NTU, which achieves (51.2) % of the optimum goal. In comparison, the water turbidity value for 95% of daily reading data of water filtered was (6.90) NTU which is larger than the goal value (5) NTU, which achieves (68.8) % of the optimum goal. The removal efficiency for previous years (2016 to 2020) was (78.5, 76, 73.5, 72, 68)%, respectively, within acceptable limits.